LANGUAGE LEARNING THROUGH SOCIAL MEDIA: EXPERIENCE, ANALYSIS, AND RECOMMENDATIONS: LANGUAGE LEARNING THROUGH SOCIAL MEDIA: EXPERIENCE, ANALYSIS, AND RECOMMENDATIONS - Bayjanov, Saparniyaz (Журнал иностранных языков и лингвистики, 2025)
The role of social media in English language learning is becoming increasingly significant, particularly among students in Uzbekistan. Platforms such as YouTube, Telegram, Instagram, and Facebook are frequently used to enhance various language skills, particularly listening and speaking. Social media offers a unique and flexible environment for learners to practice language skills outside of traditional classroom settings. These platforms provide access to authentic English content, where learners can engage with various accents, idioms, and real-life conversations, significantly contributing to vocabulary acquisition and comprehension. Furthermore, social media fosters peer interaction and collaboration, allowing learners to exchange ideas and improve their language proficiency in a low-stakes, enjoyable context. While social media can be overwhelming due to the vast amount of content available, it offers significant benefits for autonomous and interactive learning. The purpose of this study is to examine how students in Uzbekistan utilize social media to improve their English language skills, and the challenges and benefits of this approach.